Quality adjusted life years based on health and consumption: A summary wellbeing measure for cross‐sectoral economic evaluation. (22nd October 2020) - Cookson, Richard; Skarda, Ieva; Cotton‐Barratt, Owen; Adler, Matthew; Asaria, Miqdad; Ord, Toby
Abstract: We introduce a summary wellbeing measure for economic evaluation of cross‐sectoral public policies with impacts on health and living standards. We show how to calculate period‐specific and lifetime wellbeing using quality‐adjusted life years based on widely available data on health‐related quality of life and consumption and normative assumptions about three parameters—minimal consumption, standard consumption, and the elasticity of the marginal value of consumption. We also illustrate how these three parameters can be tailored to the decision‐making context and varied in sensitivity analysis to provide information about the implications of alternative value judgments. As well as providing a general measure for cost‐effectiveness analysis and cost‐benefit analysis in terms of wellbeing, this approach also facilitates distributional analysis in terms of how many good years different population subgroups can expect to live under different policy scenarios.